Current Derivative Estimation of Non-stationary Processes Based on Metrical Information; Computational Collective Intelligence; Vol. 9330 of the series Lecture Notes in Computer Science - Kochegurova E. A. Elena Alekseevna (2015, 2015)
Title screen